Early pancreatic stent placement in wire‐guided biliary cannulation: A multicenter retrospective study. Issue 6 (19th September 2018) - Hakuta, Ryunosuke; Hamada, Tsuyoshi; Nakai, Yousuke; Isayama, Hiroyuki; Kogure, Hirofumi; Takahara, Naminatsu; Mizuno, Suguru; Yagioka, Hiroshi; Togawa, Osamu; Matsubara, Saburo; Ito, Yukiko; Yamamoto, Natsuyo; et al.
Abstract: Background and Aim: Guidewire insertion to a pancreatic duct under wire‐guided cannulation (WGC) during endoscopic retrograde cholangiopancreatography (ERCP) is associated with a high incidence of post‐ERCP pancreatitis (PEP). Pancreatic stent placement followed by WGC (PS‐WGC) is considered for these cases to reduce PEP. This study was aimed to examine the effectiveness of PS‐WGC compared with repeated WGC. Methods: The consecutive data of patients without history of ERCP who underwent ERCP for biliary intervention were retrospectively collected from five centers. Patients without guidewire insertion to the pancreatic duct were excluded. Pancreatic stent was immediately placed after guidewire insertion to the pancreatic duct in the PS‐WGC group. The association between the method of biliary cannulation (PS‐WGC or repeated WGC) and PEP was analyzed using multivariable logistic regression model. Results: A total of 590 patients (183 in the PS‐WGC and 407 in the repeated WGC group) were included. PS‐WGC decreased PEP (8.7% vs 19%, P = 0.001) and improved its severity (moderate and severe PEP; 2.2% vs 6.4%, P = 0.04) compared with repeated WGC. PS‐WGC was associated with reduction of PEP in the multivariable model (Odds ratio 0.31, P < 0.001). The rates of difficult cannulation and overall successful biliary cannulation were not different between the two groups (66% vs 70%, P = 0.39 and 98% vs 96%, P = 0.21 in the PS‐WGC and repeated WGC group, respectively). Conclusions: Pancreatic stent placement followed by WGC reduced PEP in patients with guidewire insertion to the pancreatic duct during WGC for native papilla compared with repeated WGC.